THE PARTICIPATION OF CATECHOLAMINES IN THE PATHOGENESIS OF DIABETIC CARDIOMYOPATHY - Алексей Михайлович Чаулин; Юлия Владимировна Григорьева; Дмитрий Викторович Дупляков (Медицина в Кузбассе, 2020)
Under normal conditions, the sympathetic nervous system, through its main mediators (catecholamines) plays an important role in the functioning of the cardiovascular system. However, excessive and prolonged activation of the sympathetic nervous system, observed in a number of pathological conditions (stress, diabetes mellitus, etc.) causes increased levels of catecholamines in the blood and myocardium. In this review article, we consider the main mechanisms of participation of catecholamines in the pathogenesis of diabetic cardiomyopathy.